Hubungan Self Efficacy dengan Kepatuhan Menjalankan Aktivitas Fisik pada Penderita Hipertensi di Masa Pandemi Covid 19 di RW 04 Terban GK V Gondokusuman Yogyakarta Tahun 2023 - Made Wahyu Ryan Baskara; Fransisca Winandari; Chatarina Hatri Istiarini; Antonius Yogi Pratama (Syntax Idea)
Hypertension is a non-communicable disease, a person is said to have hypertension if the systolic blood pressure measurement results are â‰¥140 mmHg and the diastolic blood pressure is â‰¥90 mmHg. Hypertension that is not properly controlled has the potential to cause complications such as stroke, coronary heart disease, and kidney failure and even death. Treatment of hypertension is carried out by pharmacological and non-pharmacological methods, the efforts made are by doing physical activity. Physical activity is recommended at least 150 minutes/week with moderate intensity. Non-compliance in controlling hypertension can occur due to poor self-efficacy. To find out the relationship between self-efficacy and adherence to physical activity in people with hypertension. Correlational research design with cross sectional approach. The population is 42 people and the sample is 42 people. The sampling technique used is total sampling. The results of the chi square test obtained a p-value of 0.024 (<0.05). The contingency coefficient value is 0.329 which means it has a weak close relationship. Hypertension patients' self-efficacy and compliance with physical activities during the Covid-19 pandemic at RW 04 Terban GK V Gondokusuman Yogyakarta in 2023 is correlated.It is hoped that further researchers can examine the self-motivation of hypertension patients in controlling their disease.